2011
DOI: 10.15809/irriga.2011v16n4p360
|View full text |Cite
|
Sign up to set email alerts
|

SUPRESSÃO DE ÁGUA EM DIFERENTES FASES FENOLÓGICAS DO FEIJOEIRO (Phaseolus vulgaris L.)

Abstract: RESUMOO feijoeiro (Phaseolus vulgaris L.) é uma cultura de grande expressão no cenário econômico e social do Brasil. A hipótese do trabalho é de que a supressão do fornecimento de água em alguma ou algumas fases do desenvolvimento do feijoeiro irrigado pode resultar em redução de produtividade de, no máximo, 20%, permitindo economia de água. O objetivo do presente trabalho foi avaliar a influência da supressão de água em uma das fases fenológicas (emergência, vegetativa, floração, enchimento de grãos, maturaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…In this context, knowledge of crop sensitivity to stress due to water deficiency is fundamental to reduce impacts on production (MIORINI et al, 2011) and on irrigation costs (ALI et al, 2007). Experiments addressing this theme have shown positive results regarding melon tolerance to stress due to water scarcity (DOGAN et al, 2008;SHARMA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, knowledge of crop sensitivity to stress due to water deficiency is fundamental to reduce impacts on production (MIORINI et al, 2011) and on irrigation costs (ALI et al, 2007). Experiments addressing this theme have shown positive results regarding melon tolerance to stress due to water scarcity (DOGAN et al, 2008;SHARMA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since the difference in soil water availability during the crop cycle was small in both treatments, a similar yield would have been expected. Previous results on common beans have shown that, under stress, the plants have a reduced number of pods (Miorini et al, 2011), less pods per plant (Miorini et al, 2011;Stone et al, 1988), less grains per pod (Carvalho, 2013) and number of pods (Miorini et al, 2011). Also, the plant size was smaller independently of the event of water stress (Miorini et al, 2011).…”
Section: Crop Productionmentioning
confidence: 89%
“…Drought can modify leaf development and thus, affect grain yield by reducing the active leaf area for photosynthesis (Guimarães, 1996;Fancelli and Dourado Neto, 1991). Plant height, leaf area index, number of seeds per pod, number of pods per plant and yield are reduced in plants suffering from water stress (Monteiro et al, 2010), although the number of pods per plant was the most sensitive variable to maintain a potential yield (Guimarães et al, 2011;Miorini et al, 2011). Likewise, the bean root system develops mostly in the upper soil layer enhancing the sensitivity of the crop to water stress and reinforcing the role of irrigation water supply for proper crop development during scarce rainfall periods (Carlesso et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researches are mentioned on the effects of hydric restriction applied to different vegetative and reproductive stages, where Such Miorini et al (2011) evaluated the influence of water suppress, in comparison with irrigation in all and none growing stages of common beans (Miorini et al, 2012). In addition, Catuchi et al (2012) evaluated the interference of potassium fertilizing in physiologic parameters of two soybean cultivars, under hydric restriction (Catuchi et al, 2012), as well as Artigiani et al (2012), which aimed to evaluate yield compounds, productivity and industrial quality of rice grains of the cultivar BRS Primavera, in function of the silicon application combined with broadcast nitrogen fertilizing, in dry and irrigated conditions (Artigiani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%